Features of Multilayer Сoatings on the Basis of Zr-Y-O/Si-Al-N System - Nikonenko A. Alisa; Fedorishcheva M. V. Marina Vladimirovna; Bozhko I. A. Irina Aleksandrovna; Sergeev V. P. Viktor Petrovich; Kalashnikov M. P. Mark Petrovich (Ion-Assisted Coating Deposition. Poster Session, 2019)
Заглавие с экрана